Facilities in City Parks Can Increase the number of Visits - Pusparani, Pusparani; Nasution, Deivy Zulyanti; Maharani, Mira (PT. Riset Press International, 2025)
City parks provide recreational space and social interaction in urban areas. One park that has great potential is Bulak Teko Indah Park in West Jakarta, which offers various facilities for visitors, especially families with children. This study aims to explore how improving facilities in this park can affect visitor visits. The method used is a qualitative descriptive approach with in-depth interviews, participant observation, and documentation. Data were collected from 15 visitors and three park managers. The results showed that better facilities, such as safe play equipment, sports space, and comfortable seating, played a significant role in increasing comfort and extending the duration of visits. Safety was the main factor for families with children, while the diversity of facilities met the needs of various groups. However, there was input to increase the number of seats and improve the cleanliness of the park. Based on these findings, park managers are advised to add educational facilities, improve cleanliness, and improve accessibility for visitors with special needs. Thus, Bulak Teko Indah Park can become a more attractive and beneficial recreational destination for the community and support the development of a more inclusive and sustainable city park.